THE MARKETING MIX FACTORS THAT INFLUENCE THE DECISION OF GUEST TO VISIT IN SAKURA RESTAURANT AT MELIA BALI INDONESIA - Ni Made Sri Pratiwi; I Gusti Agung Mas Krisna Komala Sari; I Ketut Suparta (Journal of Applied Sciences in Travel and Hospitality, 2018)
This research aims are to determine the marketing mix factors that influence the decision of guests to visit in Sakura Restaurant at Hotel Melia Bali Indonesia. The problem of this research are to find out the marketing mix factors that influence the decision of the guest to visit and the most dominant factor that influence the decision of guest to visit in Sakura Restaurant at Hotel Melia Bali Indonesia. The sample selection of 100 respondents with the sampling is done by accidental sampling technique that is the sample determination technique by chance. Data processing is done with the help of software SPSS version 17.0 for windows. The analysis technique used in this research is factor analysis. Based on the research result, there are six factors that can influence the decision of guests to visit in Sakura Restaurant at Hotel Melia Bali Indonesia. The factors are service which percentage of variance of 21,949%, product which percentage of variance of 14,604 %, promotion which percentage of variance of 9,946 %, food which percentage of variance of 8,192 %, design which percentage of variance of 7,947 %, and location factor which percentage of variance of 7,843 %. The commulative of these factor are 70,481% and the value of model accuracy is 55 % with the residual of 45 %. Of thes factors. Of the six factors are found the most dominant factor is service factor consisting of 5 variables : restaurant has complete fasilities, Food rates are offered in accordance with quality of food and Restaurant facilities, The employees of sakura restaurant are providing services that can help the guest needs. The employee of restaurant providing sympathetic service, The employees of restaurant used the uniforms according with the hotel procedure.